2003
DOI: 10.1002/jcla.10072
|View full text |Cite
|
Sign up to set email alerts
|

D‐dimer and its relationship to fibrinogen/fibrin degradation products (FDPs) in disorders associated with activation of coagulation or fibrinolytic systems

Abstract: Levels of D-dimer and fibrinogen/fibrin degradation products (FDPs) are significantly elevated in patients with deep venous thrombosis, pulmonary embolism, disseminated intravascular coagulation, or other complications. The diagnosis of these disorders can be difficult, time-consuming, and expensive. Assays for the detection of FDPs and D-dimer are used in many laboratories to investigate these disorders. The aim of this study was to compare plasma D-dimer levels obtained by the immuno-turdimetric method (Liat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…D-dimer is the more appropriate laboratory test for investigating thromboembolic disease but there is no need to run D-dimer unless suspect primary fibrinogenolysis if FDP >20 μg/mL. We recently reported a relationship between D-dimer and FDP levels in the investigation of disorders associated with activation of fibrinolytic or coagulation systems, and D-dimer levels >1420 ng/mL were directly associated to positive FDP [17]. Ddimer is the smallest cross-linked fibrin degradation product.…”
Section: Discussionmentioning
confidence: 96%
“…D-dimer is the more appropriate laboratory test for investigating thromboembolic disease but there is no need to run D-dimer unless suspect primary fibrinogenolysis if FDP >20 μg/mL. We recently reported a relationship between D-dimer and FDP levels in the investigation of disorders associated with activation of fibrinolytic or coagulation systems, and D-dimer levels >1420 ng/mL were directly associated to positive FDP [17]. Ddimer is the smallest cross-linked fibrin degradation product.…”
Section: Discussionmentioning
confidence: 96%
“…D-dimer, formed on cleavage of cross linked fibrin is a specific marker of fibrinolysis.It is identified in the blood of patients with various thrombotic and thrombolytic disorders (6). It is reported that levels of D-dimer increase in patients with sepsis due to fibrinolysis (7).…”
Section: Introductionmentioning
confidence: 99%
“…It is not applicable to plasma samples containing FDP <20 lg/mL. We recently reported a relationship between D-dimer and FDP levels in the investigation of disorders associated with activation of fibrinolytic or coagulation systems, and D-dimer levels >1,420 ng/mL were directly associated to positive FDP [17]. D-dimer is the smallest cross-linked fibrin degradation product.…”
Section: Discussionmentioning
confidence: 96%